UV radiation energy consumption in curing process of epoxidized sunflower oil-organoclay hybrid coatings - Jiratumnukul, Nantana; Intarat, Ravivan (Journal of Metals, Materials and Minerals, 2017)
Epoxidized sunflower oil (ESO) can be cured with ultraviolet radiation using either cationic or hybrid initiation. The organoclay was prepared by the cationic exchange process, in which sodium ions were replaced by alkyl ammonium ions. Organoclay was incorporated into epoxidized sunflower oil UVcurable systems. The effects of diluents and types of photo initiators were studied. It was found that the formulations with a hybrid photoinitiator required less energy in the curing process than those with a cationic photoinitator. Moreover, the formulations without diluent can be cured with lower radiation energy than those with diluent.